Infection with MRSA CC398 Related to Occupational Exposure to Mink: A Case Report - Laustsen, Birgitte Hamann; Omland, Oyvind (Archives of Clinical and Medical Case Reports, 2019)
A 59-year old man was hospitalised with dyspnoea, cough and fever, which led to respiratory treatment, later complicated with large central pulmonary embolisms. The only positive finding in samples was MRSA CC398. The patient worked several times as a full-time employee at a mink farm, which was the only exposure to MRSA CC398 in the patient’s occupational history. The Danish Labour Market Insurance recognised the injury as an occupational disease; hence, exposure to LA-MRSA for working on mink farms is a new occupational risk factor in Denmark.